Pengaruh Pengalaman Kerja dan Integritas Pada Kualitas Audit dengan Etika Auditor Sebagai Variabel Pemoderasi - Sinta Dewi, Made Ayu Wilda; Widanaputra, A.A.G.P (E-Jurnal Akuntansi, 2018)
Auditors whohave more experienceon the understandingof financial statementswill be better ableto provide an explanationin the financial statements. This study aimsto determine the effect of work experience, integrity to audit quality with auditor ethicsas a moderating variable. This researchwas conducted at PublicAccounting Firm (KAP) of Bali Province registered in IndonesianInstitute of CertifiedPublic Accountant (IAPI)which amounted to Nine KAP with totalauditor as muchas 82 auditors. The question naire returns a total of 62 question naires with a total of 58question naires. Basedon the results of simple regression analysis found that work experience and integrity affect audit quality. And on the results of the moderation regressionstudy it was found thatwork experience was able tomoderate wherein the effect thatweakened the auditor'sethics on audit quality, whilethe integrity was able to moderate where the impactsre inforced the auditor'sethics on audit quality. Keywords : Employment, Integrity, Audit Quality, Auditor Ethics